Histological studies on the development of Rat's liver during embryonic life - Gheth, Ebtesam M. M.; Aboalhaj, Abdusalam M.; El-Gharbawy, Saad M. S.; Abdelaaziz, Abdullah (Al-Mukhtar Journal of Sciences, 2008)
In this study, the development of the rat's liver was investigated during the embryonic life using 39 fetuses ranged from 9-21 days of age. The hepatic diverticulum begins to appear in eleventh day of fetal life in the form of T-shaped tube evaginated into the mesoderm of the transverse septum. This diverticulum was lined by 2-3 layers of columnar and cuboidal cells that proliferated into irregular buds projected into the mesoderm of the transverse septum. At 12 day of fetal age the cells of these buds began to differentiate into the primordial liver parenchyma which arranged in the form of several masses and anastomasing cords with several blood spaces in between. The hepatic cords and cell masses were increased at the 13th day of fetal age to occupy the transverse septum. The primary hepatic sinusoids began to appear at the 12th day of fetal life in the form of irregular blood spaces. At 13 days old, its primary endothelial lining appear. These sinusoids became more differentiated with the increase of age. The Haemocytoblasts began to appear in the rat liver at the 12th day of fetal life and increased at the 13th day where they fill the lumena of the hepatic sinusoids and appeared as cell aggregations out side them. With the increase of fetal age these cells continue to increase till the time of birth. The right and left liver lobes began to appear at 12 day of fetal life. By the 16th day the liver appeared as globular structure occupy the majority of the coelom (abdominal cavity). It was formed of four lobes. In 20 days old fetuses the portal areas appeared containg branches of the portal vein, hepatic artery, lymphatic vessel and bile duct. The hepatic capsule began to appears at 12 day of fetal life. By the 16th day of fetal life the serous capsule appeared to be of one layer of mesothelial cells rested on a fibrous capsule (Glasson's capsule) which formed form a network of reticular fibers. The reticular fibers appeared in liver parenchyma and capsule during fetal life at the 17th day. The collagen fibers appeared in the capsule in 20 days old fetuses. The elastic fibers did not appear during fetal life except in the wall of blood vessels.